A High Order Iterative Scheme for a Nonlinear Kirchhoff Wave Equation in the Unit Membrane - Le Thi Phuong Ngoc; Nguyen Thanh Long (International Journal of Differential Equations)
A high-order iterative scheme is established in order to get a convergent sequence at a rate of order N (N≥1) to a local unique weak solution of a nonlinear Kirchhoff wave equation in the unit membrane. This extends a recent result in (EJDE, 2005, No. 138) where a recurrent sequence converges at a rate of order 2.